2020
DOI: 10.1002/ppul.25076
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic atrophy and dysfunction in critically ill mechanically ventilated children

Abstract: Rationale The extent of diaphragmatic atrophy and dysfunction in critically ill children from developing countries is not established. Objectives To estimate changes in ultrasound measurements of diaphragmatic thickness over the first week of mechanical ventilation. To assess magnitude and risk factors of diaphragmatic atrophy. Methods In an observational cohort study, children aged 1–18 years, requiring mechanical ventilation were included. Ultrasound measurements of diaphragmatic thickness at end‐expiration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 24 publications
1
16
0
3
Order By: Relevance
“…Optimized strategies for patient-oriented mechanical ventilation are an important and frequently discussed topic in daily pediatric intensive care and scientific studies. Various ventilation modes have been established over the years, but have repeatedly shown undesirable side effects for children [1][2][3][4]. Synchronized intermittent mandatory ventilation (SIMV) has been shown to be a lung-protective strategy in pediatric intensive care [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimized strategies for patient-oriented mechanical ventilation are an important and frequently discussed topic in daily pediatric intensive care and scientific studies. Various ventilation modes have been established over the years, but have repeatedly shown undesirable side effects for children [1][2][3][4]. Synchronized intermittent mandatory ventilation (SIMV) has been shown to be a lung-protective strategy in pediatric intensive care [5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this asynchrony increased doses of sedation in ventilated children are required as documented in a study by Baez Hernandez et al [7]. Furthermore, several studies have described diaphragmatic atrophy caused by mechanical mandatory ventilation in pediatric patients [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…6 Patients on prolonged MV experience changes in diaphragm thickness (DT), mainly atrophy, which has been seen in 44%-47% of intubated pediatric patients 7,8 with percent decline occurring at a rate ranging from 2.01% to 3.4% per day. [8][9][10] and was associated with prolonged postextubation noninvasive positive pressure ventilation (NIPPV). 11 Recognizing the potential application of bedside diaphragmatic ultrasound in objectively assessing weaning outcomes, we sought to determine the utility of using ultrasound to assess diaphragmatic characteristics during SBTs.…”
mentioning
confidence: 99%
“…Similarly, in another study, Goligher et al [45] used a different US measurement index defined as the thickness of the diaphragm (TDI); although it indicated diaphragm thinning in patients with MV, no significant correlation was detected between TDI and weaning outcomes. Afterwards, Mistri et al [47] showed that diaphragm atrophy during MV is associated with a decrease in DTF value in patients admitted to a paediatric ICU. Additionally, increased DTF was suggested as a potential predictor of successful extubation.…”
Section: Discussionmentioning
confidence: 99%